RAPID PROGRESSION OF CLAVICULAR SOLITARY PLASMACYTOMA TO MULTIPLE MYELOMA - Hantoro Gunawan; Paulus Budiono Notopuro (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Solitary plasmacytoma is a monoclonal plasma cell malignancy restricted to one tumor. Fifty percent of cases can progress to Multiple Myeloma (MM). The median time to progression is 19 months. A case about plasmacytoma advancing rapidly to MM within two months from the initial diagnosis is described. A 45-year-old male attended the Surgery Outpatient Clinic with a chief complaint of progressive swelling on the left neck for two months. Physical examination revealed a fixed, solid, 8x8 cm mass on the left supraclavicular. Fine Needle Aspiration Biopsy (FNAB) showed plasmacytoma. Surgical biopsy and immunohistochemistry confirmed the diagnosis of plasmacytoma. Ki67 index was 80%. There was no abnormality in the laboratory examination. Two months later he was admitted to the Internal Ward with anemia and kidney disorder. Serum protein electrophoresis revealed an M-spike. Bone Marrow Aspiration (BMA) showed plasma cell proliferation of 78%, which confirmed the diagnosis of MM. Solitary plasmacytoma can occur on any bone, mostly on axial bones. Solitary plasmacytoma on the clavicle is very rare, with a prevalence of 0.45% of all primary bone tumors. Diagnosis of solitary plasmacytoma relies on tissue biopsy, laboratory, radiology and bone marrow aspiration. Progression of plasmacytoma to MM can be detected from CBC and clinical chemistry results. Serum protein electrophoresis and bone marrow aspiration results confirmed the diagnosis of MM. The high proliferation index (Ki67>8%) and tumor size (>5cm) were the risk factors for the rapid progression of plasmacytoma. Early detection of systemic symptoms is critical in the management of solitary plasmacytoma.